1983
DOI: 10.1111/j.1348-0421.1983.tb00630.x
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Characterization of Tween 80‐Hydrolyzing Esterases Produced by Rapidly Growing Mycobacteria

Abstract: Tween 80-hydrolyzing esterases produced by various species of rapidly growing mycobacteria were partially purified from sonicated cell lysates by diethylaminoethyl (DEAE) cellulose and subsequent Sephadex G-150 column chromatographies. The amount of the esterase produced per gram of bacterial cells varied markedly with each species. Mycobacterium smegmatis, M. chelonei, and M. phlei were high producers and M. chitae and M. diernhoferi were low producers of Tween-hydrolyzing esterase. The resistance of each myc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In the acidophilic bacteria, Wichlacz and Unz (20) have described that Tween 80 appeared to stimulate growth of the acidophilic bacteria strains. Wichlacz et al (21) and Kishimoto et al (10) have reported that Acidiphilium facilis and A. aminolytica grew on a medium containing Tween 80 as the sole carbon source. However, the lipolytic enzyme of the acidophilic bacteria was not identified, and the enzyme production conditions were not investigated.…”
mentioning
confidence: 99%
“…In the acidophilic bacteria, Wichlacz and Unz (20) have described that Tween 80 appeared to stimulate growth of the acidophilic bacteria strains. Wichlacz et al (21) and Kishimoto et al (10) have reported that Acidiphilium facilis and A. aminolytica grew on a medium containing Tween 80 as the sole carbon source. However, the lipolytic enzyme of the acidophilic bacteria was not identified, and the enzyme production conditions were not investigated.…”
mentioning
confidence: 99%
“…Surfactants are often utilized in formulations above their critical micelle concentration (CMC) values. For example, recombinant human factor XIII is protected against both agitation and freeze-thaw-induced aggregation in the presence of polysorbate 20 at concentrations corresponding to the CMC (0.007%, w/v) [3]; however, at concentrations below this CMC value, it is not stabilized. It has also been reported that surfactant degradation products can impact the stability of the formulation [2].…”
Section: Introductionmentioning
confidence: 99%